2010
DOI: 10.1007/s10591-010-9120-8
|View full text |Cite
|
Sign up to set email alerts
|

“Broken Together”: Spirituality and Religion as Coping Strategies for Couples Dealing with the Death of a Child: A Literature Review with Clinical Implications

Abstract: The death of a child is an event that can fall into the category of uncontrollable life events, testing the limits of the ability to control of bereaved parents. The literature reviewed showed that religious/spiritual coping is a unique way of coping and may be particularly important for couples who have lost a child. When assessing the couples' coping strategies, marital therapists would be wise to look for religious/spiritual mechanisms that can be employed in the therapeutic process. Furthermore, the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…While this can be considered unlikely, I hedge against this possibility by using the second indicator of contingency, Experience of death, which can hardly be argued to be driven by religious interpretation. Moreover, previous research suggests that experience of death constitutes a contingency experience that can contribute to increased religiosity (as, for example, shown by Zapata 2018) and that religion is used to cope with experiences of death in close social proximity (Ungureanu and Sandberg 2010). In Section 6.2, I scrutinize the validity of the exclusion restriction for our case by evaluating potential alternative pathways from contingency experience to labor market performance in the data.…”
Section: Contingency Experience As An Instrumental Variable For "Treamentioning
confidence: 99%
“…While this can be considered unlikely, I hedge against this possibility by using the second indicator of contingency, Experience of death, which can hardly be argued to be driven by religious interpretation. Moreover, previous research suggests that experience of death constitutes a contingency experience that can contribute to increased religiosity (as, for example, shown by Zapata 2018) and that religion is used to cope with experiences of death in close social proximity (Ungureanu and Sandberg 2010). In Section 6.2, I scrutinize the validity of the exclusion restriction for our case by evaluating potential alternative pathways from contingency experience to labor market performance in the data.…”
Section: Contingency Experience As An Instrumental Variable For "Treamentioning
confidence: 99%
“…Walsh (2009) noted that spirituality is still an important consideration in our clients’ lives. When spiritual beliefs are a part of how a couple is creating meaning in their relationship, it often influences every aspect of their life (Mahoney, 2010; Pargament, 2009; Ungureanu & Sandberg, 2010). Therapists should take extra care around the issues of spirituality as Watkins van Asselt and Baldo Senstock (2009) found that the more aware therapists were spiritually, the greater their ability to recognize a client’s spiritual concerns and integrate them into the treatment.…”
Section: Spirituality As An Important Consideration For Couples Effecmentioning
confidence: 99%
“…Beliefs are also externally established and provide standards by which adherents are encouraged to live. According to Nedumaruthumchalil (), “religion is a human activity and not an activity of the Supreme Being” (p. 16), and Walsh () described religion as an “organized belief system that includes shared, institutionalized moral values” (as cited in Ungureanu & Sandberg, , p. 303). By contrast, spirituality is described as individual, universal and innate, with an emphasis on the subjective feeling of connectedness to a higher power rather than adherence to specific codes or standards.…”
Section: Religion and Spirituality Discourse In Family Researchmentioning
confidence: 99%